Signatures of quenching in dwarf galaxies in local galaxy clusters: A comparison of the galaxy populations in the Virgo and Fornax clusters - Janz Joachim; Salo Heikki; Su Alan H; Venhola Aku (EDP Sciences, 2022)
Context. The transformation of late-type galaxies has been suggested as the origin of early-type dwarf galaxies (typically M⋆ ≤ 109 M⊙) in galaxy clusters. Based on deep images, Venhola and colleagues analysed correlations between colour and surface brightness for galaxies in the Fornax cluster binned by luminosity or stellar mass. In the bins with M⋆ < 108 M⊙, the authors identified a correlation of redness with fainter surface brightness and interpreted it as a consequence of the quenching of star formation by ram pressure stripping in the dwarf galaxies.
Aims. This study carries out a similar analysis for the Virgo cluster. The analysis for both clusters is then used to compare the Virgo and Fornax clusters, for which the ram pressure is expected to have different strengths. The purpose of this is to scrutinise the ram pressure interpretation from the other study and search for differences between the clusters that reflect the different ram pressure efficiencies, which would either support or weaken this interpretation. Ultimately, this could help weigh the importance of ram pressure stripping relative to other transformative processes in the shaping of the dominant early-type dwarf galaxy population.
Methods. We extend the analysis of colour versus surface brightness binned by stellar mass to higher masses and a wider range of optical colours. The results, in particular at low stellar mass, are compared to predictions of stellar evolution models. Benefitting from larger sample sizes, we also analyse late- and early-type galaxies separately. This analysis is carried out for the Virgo and Fornax clusters, and the colour versus surface brightness relation, as well as other properties of the two clusters’ galaxy populations, are compared.
Results. While the colour–surface brightness diagrams are remarkably similar for the two clusters, only the low-mass late-type galaxies are found to have slopes consistent with a fading and reddening following the quenching of star formation. For the early-type galaxies, there are no (or only weak) correlations between colour and surface brightness in all mass bins. Early- and late-type galaxies in both clusters have comparable sizes below a stellar mass of M⋆ ≲ 108 M⊙. The colour and size scaling relations are very similar for the Virgo and Fornax clusters. However, Virgo features a lower fraction of early-type or red galaxies despite its higher mass.
Conclusions. The similarity of early-type dwarfs and low-mass late types in size at the masses M⋆ ≲ 108 M⊙ as well as the overall consistency of the colour–surface brightness correlation with fading stellar populations support a scenario of transformation via the quenching of star formation, for example by gas removal. However, the lack of this imprint of an ageing stellar population on the early-type dwarfs themselves calls for some additional explanation. Finally, the Virgo cluster is an atypical cluster with a comparably low fraction of quiescent early-type galaxies at all galaxy masses despite its large cluster mass.
Key words: galaxies: clusters: general / galaxies: evolution / galaxies: dwarf / galaxies: stellar content / galaxies: clusters: individual: Virgo / galaxies: clusters: individual: Fornax
© ESO 2021